VALIDITY OF ELECTRONIC AGREEMENTS WITH DIGITAL SIGNATURES FROM THE PERSPECTIVE OF INDONESIAN CIVIL LAW - Naib (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the validity of electronic agreements with digital signatures from the perspective of Indonesian civil law, based on the Civil Code (KUHPerdata) and related regulations such as Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) and Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions (PP PSTE). Using a normative legal research method with a statutory and conceptual approach, this study discusses the fulfillment of the valid requirements of an agreement according to Article 1320 of the Civil Code, namely agreement, capacity, certain things, and lawful cause, in an electronic context. Digital signatures, which utilize cryptography for authentication, integrity, and non-repudiation, are recognized as valid if they meet the requirements of Article 11 of the ITE Law, especially those certified by an Electronic Certification Provider. In addition, the evidentiary power of digital signatures as an extension of written evidence (Article 5 of the ITE Law) varies; certified signatures have a higher authentic value than uncertified ones. The conclusion states that electronic agreements are valid and have legal certainty, although there are limitations for certain formal documents, and recommends the use of certified signatures to reduce the risk of civil disputes.